Adverbs and adverbial adjuncts at the interfaces - Kiss, Katalin É (Interface explorations ;, 2009)
This book aims to clarify - on the basis of mainly Hungarian data - basic issues concerning the category 'adverb', the function 'adverbial', and the grammar of adverbial modification. It argues for the PP analysis of adverbials, and claims that they enter the derivation via left- and right-adjunction. Their merge-in position is determined by the interplay of syntactic, semantic, and prosodic factors. The semantically motivated constraints discussed also include a type restriction affecting adverbials semantically incorporated into the verbal predicate, an obligatory focus position for scalar a.